Editorial - Chau, Meng Huat (Journal of Modern Languages, 2019)
The publication of Volume 29 marks the end of 2019, and a change to the JML editorial team. Zuraidah Mohd Don has stepped down from her role as Editor-in-Chief after many years of dedicated service, and we welcome a largely new board of editorial members, who are from Brunei, China, the UK as well as Malaysia.